Effect of Rice Husk Reinforcement on Low Density Polyethylene: Effect of Rice Husk on Polyethylene (Biological Sciences - PJSIR, 2023)
Low density polyethylene (LDPE) is one of the most common commodity thermoplastics and covers a broad range of applications whereas rice husk is the coating on a seed or grain of rice. Different studies have been done to show the effect of rice husk on high density polyethylene and linear low density polyethylene the limited data is available that shows the effect of rice husk on the properties of LDPE.  In this research, rice husk is reinforced in LDPE by using two roll mills as mixing equipment for uniform mixing, the roller is heated at a temperature of 120°C and the particle size of the rice husk is 60 µm. The uniformly mixed material is converted into the shape of the sheet by using a hot press machine. The temperature of the mold is 160°C and the pressure is about 200 psi. The sample is then cooled at room temperature. The sample was characterized by tensile testing, tear testing, hardness testing, thermal gravimetric analysis and Fourier Transform Infrared Spectroscopy. According to the results, the thermal stability of reinforced material is increased as compared to pure LDPE. The hardness, tensile strength and modulus were also increased with a decrease in elongation and tear resistance. Fourier Transform Infrared Spectroscopy results indicate no change in the chemical properties of the matrix, the composite formed was just a physical mixture of rice husk. Overall the reinforcement of rice husk in LDPE increased the thermal stability and mechanical properties of the sample. The cost of rice husk is also lower than LDPE. So, the addition of rice husk will also decrease the overall cost of the product.